Development The Discord-Based Learning Media as a Digital Platform for Communication, Collaboration, and Student Interaction - Muhammad Alif; Munawwarah Munawwarah; Muhammad Naufal (Universitas Negeri Semarang, 2026)
This study aimed to develop Discord-based learning media as a digital platform for communication, collaboration, and student interaction in the learning process. The study employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The developed product was organized as a structured Discord server containing channels for announcements, discussion, quizzes, assignment submission, and learning materials. The product was evaluated through expert validation and a limited trial involving students of Class XII 2 at SMAN 3 Polewali. Data were collected through questionnaires, supported by observation and interviews, and analyzed using descriptive qualitative and quantitative techniques based on a five-point Likert scale. The results showed that the developed media were considered feasible for learning use. Media expert validation yielded an average score of 4.2 (84%), categorized as good, while material expert validation yielded 4.6 (92%), categorized as very good. Student responses also indicated positive acceptance, with an average score of 4.02 (80.8%), categorized as good. The highest student rating was found in interest in the media, whereas ease of use received the lowest score. These findings imply that Discord has potential as an alternative digital learning medium that can support communication, collaboration, and student interaction, although technical guidance and accessibility support are needed to optimize its implementation in educational settings.